Higher expression of deoxyuridine triphosphatase (dUTPase) may predict the metastasis potential of colorectal cancer. Issue 4 (3rd December 2008) - Kawahara, A; Akagi, Y; Hattori, S; Mizobe, T; Shirouzu, K; Ono, M; Yanagawa, T; Kuwano, M; Kage, M
Abstract : Aims: 5-Fluorouracil (5-FU) is one of the most widely used anticancer drugs; however, the activity of 5-FU is determined by the presence of several enzymes that limit its activation or degradation, and these include dihydropyrimidine dehydrogenase (DPD), orotate phosphoribosyl transferase (OPRT), thymidylate synthase (TS), thymidine kinase (TK), thymidine phosphorylase (TP) and deoxyuridine triphosphatase (dUTPase). The aim of this study was to compare the expression levels of these enzymes between the primary colorectal cancer of patients with and without distant metastases. Furthermore, there was a comparison of these expression levels between the primary tumour and the corresponding metastasis. Methods: Of 55 patients with colorectal cancer, 20 had no metastasis and the other 35 had distant metastasis. A strong expression was classified as positive, while weak to moderate or no expression was negative by immunohistochemistry. Results: Of the six 5-FU-related enzymes, the numbers of patients with expression of dUTPase (54% versus 15%; p = 0.005), TK (26% versus 0%; p = 0.019) and DPD (17% versus 45%; p = 0.033) were significantly different in those with primary tumours with metastasis compared with those with non-metastasis, respectively. The altered expression of OPRT (34.3%), TS (40.0%) and dUTPase (42.9%) was significantly greater from primary to metastasis among the 35 patients with metastasis. By contrast, the expression of OPRT, TS and dUTPase was decreased in 6, 5 and 7 patients, respectively, in metastatic sites. Conclusions: From this comparative study of the six 5-FU-related enzymes in colorectal cancer, the expression of dUTPase was most significantly different between primary tumours and their corresponding metastatic tumour. It is suggested that dUTPase may be a predictive biomarker for the metastatic potential of colorectal cancer.